Profiling type I and II interferon responses reveals distinct subgroups of pediatric patients with autoinflammatory disorders - Anaïs Nombel, PharmD; Magali Perret, MSc; Sophie Trouillet-Assant, PhD; Marine Villard, PhD; Christine Lombard, PharmD; Lorna Garnier, PharmD; Anne-Perrine Foray, MD, PhD; Sarah Benezech, MD; Remi Pescarmona, PharmD; Samira Khaldi-Plassart, PhD; Thierry Walzer, PhD; Alexandre Belot, MD, PhD; et al. (Journal of Allergy and Clinical Immunology: Global)
Background: Elevation of type I interferon (IFN-I) is characteristic of a group of diseases known as type I interferonopathies. Several technologies are available to monitor IFN-I, but there is no consensus on their routine use in medical laboratories. Objective: We aimed to compare the performance of two technologies for this purpose: NanoString, which monitors messenger RNA expression of interferon-stimulated genes (ISGs), and Simoa, which quantifies IFN-α2 protein in an ultrasensitive way. We also designed a NanoString assay to monitor type II ISGs and tested its value to discriminate clinical conditions. Methods: A total of 196 samples from patients with diseases associated or not with IFN-I pathway activation were analyzed by NanoString and Simoa. Results: The comparison between NanoString IFN-I score and IFN-α2 Simoa revealed a r2 coefficient of 0.55. We identified IFI27, IFI44L, and SIGLEC1 as the ISGs most closely related to IFN-α2 concentration. Nineteen samples had a positive IFN-I score but undetectable IFN-α2. These samples were also positive according to IFN-II score, pointing to IFN-II as the primary ISG inducer in corresponding patients. By measuring IFN-I and IFN-II scores in a subset of patients with systemic lupus erythematosus and systemic juvenile idiopathic arthritis, we identified two subgroups of patients in whom IFN-I and IFN-II were dominant. Conclusion: Both IFN-α2 quantification and NanoString reliably distinguish type I interferonopathies from other diseases. Type I and II interferons induce different transcriptomic signatures in vitro and in vivo, and our results highlight the value of monitoring both IFN-I and IFN-II in interferon-related diseases.